The Production of Striped Catfish (Pangasius hypophthalmus) In Intensive Cultivation Reviewed Water Quality Parameters of Red Yellow Podzolic In Different Age - Nirmala '; Saberina Hasibuan; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
This study aims to determine the striped catfish production intensive cultivation reviewed from parameters of water quality pond with a red-yellow podzolic in different ages. The method used in this study is the experimental method using a completely randomized design (CRD) using 1 factor, 4 levels of treatment and 3 replications, , with the treatment are: P1 (intensive pond of catfish aquaculture aged 0-5 years), P2 (intensive pond of catfish aquaculture aged 6-10 years), P3 (intensive pond of catfish aquaculture aged 11-15 years) and P4 (intensive pond of catfish aquaculture aged 16-20 years). The results showed that the striped catfish production in P4 (pond aged 16-20 years) is the best treatment which has a high production of 6.4 kg/m2, with the survival rate of 66,7% and low feed conversion ratio of 1.9%, and supported by water quality parameters were classified as good, namely: temperature between 27,600C, the brightness of 24.03 cm, 6.4 to 7.3 of pH, 3.74 mg/L of oxygen demand, ammonia of 0.21 mg/L, orthophosphate 1.05 mg/L, nitrate 1.03 mg/L, alkalinity total 100.5 mg/L, free carbon dioxide of 9.49 mg/L, and total organic material of 7.23 mg/L. Parameter water quality is relatively good for striped catfish farming.Keywords: Production of striped catfish (Pangasius hypophthalmus), Water Quality